Transformational Leadership In Building Sustainable Human Resources In The Digital Era - Vivi Indriani; Trias Setyowati; Nurul Qomariyah (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
The rapid advancement of digital technology has reshaped organizational systems, work structures, and human resource practices across all sectors. As automation, artificial intelligence, and data-driven processes increasingly define operational models, organizations face the urgent challenge of sustaining a capable, motivated, and future-ready workforce. In this context, leadership becomes a determining factor in navigating digital transformation effectively. This study examines the role of transformational leadership in building sustainable human resources in the digital era. Transformational leadership characterized by vision, inspiration, intellectual stimulation, and individualized consideration aligns strongly with the demands of digital transformation, where continuous learning, adaptability, and innovation are essential. Drawing on an integrative literature review, this study synthesizes findings from recent empirical and conceptual works to identify how leadership influences employee motivation, skill development, and long-term organizational sustainability. The analysis shows that transformational leaders foster intrinsic motivation, strengthen psychological readiness for change, and promote a culture of learning and collaboration. These leadership behaviors help reduce resistance to technological disruption and support the development of digital competencies. Moreover, transformational leadership reinforces human-centered values, ensuring that technological advancement is balanced with employee well-being and organizational ethics. The findings highlight that sustainable human resource development depends not only on technological investment but also on leadership capacity to inspire trust, cultivate a supportive culture, and guide employees through ongoing change. This study concludes that transformational leadership serves as a strategic driver for creating resilient, innovative, and sustainable human resources capable of thriving in the digital era.